Omuz Ağrıları - Kutluca, Abdurrahman; Gökbelen Bilen, Duygu; Ekinci, Duygu; Yaprak Taş, Esra; Baygül Atalay, Yurdagül; Kaplan, Hüseyin; Batın, Sabri; Koçer, Derya; Doğan, Serap; Etleç, Muhammet Mustafa; Ekinci, Yakup; Kahraman, Murat; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-